The Molecular Mechanisms of Ferroptosis and Its Role in Blood-Brain Barrier Dysfunction - Chen, Xiaoshu; Pang, Xinru; Yeo, Abrey J.; Xie, Siwen; Xiang, Mengting; Shi, Bin; Yu, Gongchang; Li, Chao (Frontiers in Cellular Neuroscience, 2022)
The blood-brain barrier (BBB) is a selective, semi-permeable layer of endothelial cells that protects the central nervous system from harmful substances circulating in blood. It is one of the important barriers of the nervous system. BBB dysfunction is an early pathophysiological change observed in neurodegenerative diseases. Ferroptosis is a novel cell death formula caused by iron-mediated lipid peroxidation accumulation, which has recently attracted more attention due to its possible role in nervous system disorders. Studies have shown that lipid peroxidation and iron accumulation are related to the barrier dysfunction, especially the expression of tight junctions protein. Therefore, it is necessary to investigate the relationship between ferroptosis and the BBB which may reveal new targets for the treatment of brain diseases.